LA REALIDAD DE LA TRADUCCIÓN ACADÉMICA EN IRAQ (Journal of the College of Languages (JCL), 2015)
Studying translation as academic article has cultural motive side by side academic aim to establish a professional generation that have the ability to serve labor market .And because translation is important in many sectors in the society such as technology, science, popular institutions, tourism and political and legal relations between countries.Our investigation concentrate on the articles of translation teaching in fourth class/ Spanish Department/ College of Languages/ Baghdad University for five years in order to evaluate the level of utility of creating translators and interpreters after graduation .From 2009 until 2014 we saw continuous yearly exchanging in teaching articles by many professors with different levels , in our point of view have weaken the level of fourth class students.And we tried to form fixed articles of teaching translation in general in order to give students many practices in different sectors of professional translation to prepare them to work as translators.